KIT COLORIMÉTRICO PARA DETECÇÃO DE METANOL EM ETANOL COMBUSTÍVEL PARA O MONITORAMENTO DA QUALIDADE DE COMBUSTÍVEIS - Guilherme B. C. Martins (Química Nova, 2015)
A colorimetric kit for methanol detection in ethanol-containing fuels and ease of use in the field was developed and tested. The analysis can detect the presence of methanol in fuels when exceeding specification (0.5% v/v) in about 20 min and its simple instrumentation does not require a specialist. The kit method was successfully validated at gas stations located in São Paulo State and the Federal District.